miR-1/133a clusters cooperatively specify the cardiomyogenic lineage by adjustment of myocardin levels during embryonic heart development. - Katharina Wystub (Public Library of Science (PLoS), 2013)
miRNAs are small RNAs directing many developmental processes by posttranscriptional regulation of protein-coding genes. We uncovered a new role for miR-1-1/133a-2 and miR-1-2/133a-1 clusters in the specification of embryonic cardiomyocytes allowing transition from an immature state characterized by expression of smooth muscle (SM) genes to a more mature fetal phenotype. Concomitant knockout of miR-1-1/133a-2 and miR-1-2/133a-1 released suppression of the transcriptional co-activator myocardin, a major regulator of SM gene expression, but not of its binding partner SRF. Overexpression of myocardin in the embryonic heart essentially recapitulated the miR-1/133a mutant phenotype at the molecular level, arresting embryonic cardiomyocytes in an immature state. Interestingly, the majority of postulated miR-1/133a targets was not altered in double mutant mice, indicating that the ability of miR-1/133a to suppress target molecules strongly depends on the cellular context. Finally, we show that myocardin positively regulates expression of miR-1/133a, thus constituting a negative feedback loop that is essential for early cardiac development.